Estimating the risk of zoonotic transmission of swine influenza A variant during agricultural fairs in the United States: a mathematical modeling - Pittman Ratterree, Dana C.; Chitlapilly Dass, Sapna; Ndeffo-Mbah, Martial L. (Frontiers in Veterinary Science, 2025)
IntroductionAgricultural fairs offer a unique interface between humans and swine. We investigate the transmissibility of influenza A variant from pigs to humans using epidemiological data from a 2011 zoonotic outbreak of an influenza H3N2 variant during an agricultural county fair in Pennsylvania.MethodsWe developed a mathematical model for the transmission of a swine influenza pathogen among pigs and humans at an agricultural fair. We fitted our model to the outbreak data to estimate zoonotic transmissibility. We considered nine data-driven scenarios of swine-to-swine basic reproductive number (R0) and the number of infected pigs at the start of the fair, and we simulated the zoonotic outbreak dynamics.ResultsWe estimated the probability of swine-to-human H3N2v transmission per minute of swine contact for which our model best fitted the data. The probability of transmission of H3N2v per minute of contact with swine among club members was estimated to vary from 0.029 (95% confidence interval (CI): 0.028–0.030), when R0 = 2 with 1 initially infected pig, to 0.00099 (0.00095–0.00102), when R0 = 6 with 5 initially infected pigs. For attendees, we showed that the probability equals 0.0168 (95% CI: 0.0167–0.0169), when R0 = 2 with 1 initially infected pig, and 0.00371 (95% CI: 0.00368–0.00373), when R0 = 2 with 5 initially infected pigs. For all scenarios, we estimated H3N2v infection prevalence among club members and attendees to average 12 and 0.7%, respectively.DiscussionThese results show that the transmission risk may vary substantially between club members and attendees and with the underlying disease transmission among pigs. Although fair attendees may have a small transmissibility risk, annual fair attendees represent a large population likely to experience zoonotic events and facilitate the emergence of a potential pandemic influenza variant.